Germany's Solar Cell Promotion: An Unfolding Disaster - Manuel Frondel; Christoph M. Schmidt; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This article revisits an analysis by Frondel, Ritter and Schmidt (2008) of Germany's Renewable Energy Act, which legislates a system of feed-in tariff s to promote the use of renewable energies. As in the original article, we argue that Germany's support scheme subsidizes renewable energy technologies not based on their long-term market potential, but rather on their relative lack of competitiveness, with the photovoltaics (PV) technology enjoying high feed-in tariffs, currently over double those of onshore wind. The result is explosive costs with little to show for either environmental or employment benefits. Indeed, we document that the immense costs foreseen by Frondel and colleagues have materialized: Our updated estimate of the subsidies for PV, at 100 Bn exteuro, exceeds their expectations by about 60%. Moreover, with installed PV capacities growing at a rapid rate, these costs will continue to accumulate, diverting resources from more cost-effective climate protection instruments.
Keywords: Q28; Q42; Q48; 330; Energy policy; employment effects; climate protection